The Influence of Lecturer Competence, Lecturer Creativity, and Utilization of E-Learning Media (E-MTU) on Student Understanding at Universitas Mahkota Tricom Unggul During the Covid-19 Pandemic - Sungguh Ponten Pranata (Institute of Computer Science (IOCS), 2022)
The purpose of this study was to determine the effect of lecturer competence, lecturer creativity, and MTU e-learning media on student understanding at Universitas Mahkota Tricom Unggul during the Covid-19 pandemic. The path approach and associative quantitative are used because the data that will be used to analyze the relationship between variables are expressed in numbers. This study connects lecturer competence, lecturer creativity, and e-learning media E-MTU. Where the sample in this study amounted to 115 respondents. Collecting data using a questionnaire with a Likert scale that has been tested for validity and reliability. The data analysis used is Path Analysis with the data analysis method using Smart PLS. The results of this study indicate that: (1) The competence of lecturers has a positive and significant effect on students' understanding of 0.471 with a P-Value of 0000 and tcount of 3.749 > ttable 1.96. (2). Lecturer creativity has a positive and significant effect on student understanding of 0.467 and P-Value of 0.004 and tcount in this study is 2.764 > ttable 1.96 (3). The competence of lecturers through the M-TU e-learning media has a positive and significant effect on students' understanding of management by 0.305 and P-values ​​of 0.012. tcount in this study the results obtained were 2,625 > ttable 1.96. (4). Lecturer creativity through E-Learning E-MTU has a positive and significant effect on students' understanding of management by 0.351 and P-Value by 0.002. for the calculation of tcount in this study, the results obtained were 3.765 > ttable 1.96.